The slowdown in Asia’s international Trade and its causes - Vu, Thi Kim Anh (2020)
General objective: Identify and recognize the changing trends in international trade in Asia as well as find out the causes of the slowdown in Asia’s trade. Specific objectives: - Find out how the slowdown in trade is happening in Asia. - Find out the changing trend in Asia's Trade by commodity group. - Find out the changing trend in Asia's Trade by partner. - Find out the causes of the slowdown in Asia’s Trade. - Make policy implications in this context to identify and mitigate the negative impact of this phenomenon.